PERANAN PARTAI POLITIK SEBAGAI PILAR DEMOKRASI PASCA REFORMASI DI INDONESIA - Romli Mubarok (Fakultas Hukum Universitas 17 Agustus (UNTAG) Semarang, 2012)
Political parties initially formed on the basis of a desire to unite the various groups of people who have the same vision and mission, so that the mind and their orientation can be consolidated. Departing from that, it can be described that political parties are organized groups, where members have an orientation, values , and ideals of the same, which aims to realize these goals by acquiring political power and seize the political. In order to achieve the objectives of political parties should be able to carry out their functions properly. The functions of political parties are as follows: (1) Means of Political Communication, (2) Means of Political Socialization, (3) Means of Political Recruitment, and (4) Means Regulatory Conflicts. Post-reform in Indonesia, political parties are not able to function properly as a pillar of democracy. Several factors could be the cause of the failure of political parties in Indonesia to perform its functions, namely (1) the party system in Indonesia, (2) cultural elitism, and (3) political pragmatism itself. To improve the conditions said, one of the political parties as democratic institutions that play an important role in the democratic process should be able to provide political education for the people of Indonesia, and to be able to put its position actively and creatively in order to carry out the duties and functions both in the preparation for the general election and in the aftermath of the elections.